A new species of sucking louse Hoplopleura villosissima n. sp. (Psocodea: Phthiraptera: Hoplopleuridae) and a new host record of the spiny rat louse Polyplax spinulosa Burmeister, 1839 (Psocodea: Phthiraptera: Polyplacidae) from the long-haired rat Rattus villosissimus Waite (Rodentia: Muridae) in Australia - Wang, Wei; Weaver, Haylee J; Song, Fan; Durden, Lance A; Shao, R (Parasites & Vectors, 2018)
Background: The sucking louse fauna of endemic Australian rodents has been under-studied for decades. Sixty-five species of native rodents have been recorded in Australia. However, only 11 species of lice have been reported from 11 species of endemic Australian rodents. Results: We describe a new species of sucking louse, Hoplopleura villosissima Wang (Psocodea: Phthiraptera: Hoplopleuridae), and report a new host record of the spiny rat louse, Polyplax spinulosa Burmeister, 1839 (Psocodea: Phthiraptera: Polyplacidae), from the long-haired rat, Rattus villosissimus Waite (Rodentia: Muridae), which is endemic to Australia. Conclusions: This study is the first record of sucking louse from R. villosissimus and the first record of a species of Polyplax Enderlein, 1904 from an endemic Australian rodent. This study brings the total number of sucking louse species in endemic Australian rodents from 11 to 13. Previously, only the introduced brown rat, Rattus norvegicus Berkenhout and the black rat, Rattus rattus Linnaeus were recorded as the hosts of P. spinulosa in Australia. Because R. villosissimus overlaps with R. rattus in distribution but not with R. norvegicus, we propose that P. spinulosa transferred to R. villosissimus from R. rattus.